FOSTERING INTUITIVE COMPETENCE IN CADETS THROUGH MATHEMATICAL THINKING AND CREATIVITY - Istam Yarikulovich Rakhmonov (Bright Mind Publishing, 2025)
This article explores the development of intuitive competence in cadets by enhancing mathematical thinking and promoting a creative approach in the educational process. The interrelation between intuition and mathematical thinking is analyzed, highlighting the role of creative thinking in intuitive decision-making. Methods for developing mathematical thinking and fostering creativity among cadets are presented, along with practical pedagogical examples illustrating how solving mathematical problems can cultivate intuitive thinking skills. The article concludes with recommendations for effective teaching practices.
Keywords: Intuition, intuitive competence, mathematical thinking, creativity, creative approach, pedagogical methods, cadets.